Differential expression of bovine major acute phase proteins, cytokines and metabolic indicator genes in clinical endometritis cows - MANIMARAN, AYYASAMY; KUMARESAN, ARUMUGAM; SARKAR, SOUVENDRA NATH; BOYA, SANJANNA; SREELA, L; MOOVENTHAN, P; WANKHADE, PRATIK R (The Indian Journal of Animal Sciences, 2019)
Among the uterine diseases, clinical endometritis (CE) is a major challenge to livestock farming as it causes sub- or infertility problems in dairy animals. The aim of this study was to evaluate the expression of cytokines (IL- 1Î², TNF-Î±, IL-6, and IL-8), acute phase proteins [APPs; haptoglobin (Hp), serum amyloid A (SAA) and alpha-1 acid glycoprotein (AGP)] and energy indicators [leptin and insulin-like growth factor (IGF)-1] genes in uterine tissue of CE affected cows. The uterine biopsy from CE cows (4) and non-endometritis cows (4) was processed for quantitative real-time PCR to study the mRNA expression of these innate immune molecules. We observed that mRNA expression of SAA, IL-1Î², IL-8 and leptin genes were significantly up-regulated while, TNF-Î± and IGF-I genes were significantly down-regulated in CE cows. It can be concluded that bovine APPs, cytokines and energy indicators genes are differentially expressed in CE affected cows.